Experimental Substantiation of Therapeutic Hypothermia and Cell Therapy Application at Dyscirculatory Encephalopathy in SHR Rats. Part 1. Spontaneously Hypertensive SHR Rats as a Model of Dyscirculatory Encephalopathy - Aidarova, Victoria S.; Babiichuk, Vladislav G.; Kudokotseva, Olga V.; Naumova, O. V.; Lomakin, Ivan I.; Protsenko, E. S. (Problems of Cryobiology and Cryomedicine, 2018)
The possibility of using spontaneously hypertensive rats (SHR) as an adequate of dyscirculatory encephalopathy model was investigated. Morphological, morphometric parameters and intensity of processes of lipid peroxidation (malonic dialdehyde (MDA) content) in the brain tissue of white outbred rats (assumed as a normotensive control) and SHR rats were assessed, as well as their blood pressure, blood viscosity and hematocrit were analyzed. In the SHR rats, the changes in architectonics of the brain vascular bed and degenerative-dystrophic lesions of the brain tissue were noted on the background of significantly high blood pressure, increased blood viscosity, reduced oxygen delivery to tissues, and high MDA content (compared with normotensive control). It has been established that SHR rats can be used for developing the ways of correction of pathologically changed brain structures using the methods of craniocerebral hypothermia as well as introduction of cryopreserved cells of cord blood. Â Probl Cryobiol Cryomed 2018; 28(3): 224â€“236